2017
DOI: 10.1111/sjtg.12177
|View full text |Cite
|
Sign up to set email alerts
|

Governing industrial estates on Jakarta's periurban area: From shadow government to network governance

Abstract: This article investigates the way in which periurban politics have mediated foreign direct investment relocations and facilitated the spatial restructuring of the Jakarta Metropolitan Area (JMA), one of the largest and fastest‐growing megaurban regions in Asia. We conducted a series of in‐depth interviews in Cikarang, the largest, most developed industrial estate corridor in the urban periphery of JMA. We identified institutional settings, power struggles and governance mechanisms underlying the industrial est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
0
16
0
4
Order By: Relevance
“…The first and perhaps most crucial one is the limited capacity that Bekasi District government has in managing the territorial development processes, particularly in the context of globally induced industrialization. This can be linked to a ‘rural’ type of organizational administration associated with ‘district’ ( kabupaten ) governments (Hudalah, ) and the rapid rotation of the state apparatus of Bekasi District government that often inhibits internal learning processes (Purwaningrum, : 76 − 88). Besides, in some of our interviews, it was indicated that there is lack of local leadership that is able to facilitate better coordination and communication among different governmental units for industrial‐based development.…”
Section: Discussion: Strategic Coupling In Bekasi District?mentioning
confidence: 99%
See 1 more Smart Citation
“…The first and perhaps most crucial one is the limited capacity that Bekasi District government has in managing the territorial development processes, particularly in the context of globally induced industrialization. This can be linked to a ‘rural’ type of organizational administration associated with ‘district’ ( kabupaten ) governments (Hudalah, ) and the rapid rotation of the state apparatus of Bekasi District government that often inhibits internal learning processes (Purwaningrum, : 76 − 88). Besides, in some of our interviews, it was indicated that there is lack of local leadership that is able to facilitate better coordination and communication among different governmental units for industrial‐based development.…”
Section: Discussion: Strategic Coupling In Bekasi District?mentioning
confidence: 99%
“…ZONI can be seen as a means for transforming and boosting the locational competitiveness from sites/estates level to Cikarang level. Hudalah (: 67) describes that through ZONI, ‘the industrial estates attempted to enhance communication, cooperation and partnerships with the governments’. For instance, the signing of the MoU of ZONI in 2006 involved key state parties, including the Ministry of Public Works, West Java provincial government, Bekasi District government, and PT Jasa Marga (a state‐owned company responsible for toll‐road development and management).…”
Section: The Role Of Local Institutional Actorsmentioning
confidence: 99%
“…The plan emerged in a context of a continuously transforming regime, following more than a decade of halting democratization processes, and shifting modes and scales of governance (Hudalah, ). Many in Jakarta hold a perception that in the absence of a strong central state, the government is unable to manage urban problems (Mohsin, ).…”
Section: Hyper‐planning: Political Functions Of Planning the Global Smentioning
confidence: 99%
“…Oleh karena itu, tata kelola metropolitan cenderung memiliki karakteristik yang terfragmentasi sehingga sangat rentan terhadap kesulitan dalam manajemen permasalahan lintas wilayah. Berkaitan dengan persoalan desentralisasi, lemahnya tata kelola oleh pemerintah telah membuka ruang yang sangat luas bagi privatisasi dan kontrol oleh swasta sebagai pemerintah bayangan dalam pembangunan di kawasan Jabodetabek (Firman & Fahmi, 2017;Hudalah, 2017). Berbagai persoalan tersebut menghasilkan segregasi baik pekerjaan maupun spasial pada transformasi kawasan peri-urban Jabodetabek (Winarso, Hudalah, & Firman, 2015).…”
Section: A Pendahuluanunclassified
“…Proses desentralisasi kekuasaan telah menghadirkan tantangan baru, dimana keterbatasan kemampuan pemerintah lokal dalam membangun jaringan kerjasama dengan pemerintah disekelilingnya dimanfaatkan oleh sektor privat untuk mengubah struktur dan pola spasial. Dalam kasus di JMA, kondisi ini menyebabkan pembangunan infrastruktur yang seharusnya dapat dilakukan secara komprehensif untuk meningkatkan keterhubungan antar wilayah justru menyebabkan terjadinya fragmentasi antar daerah (Hudalah, 2017). Fragmentasi tersebut tercermin dalam pola komuter yang terjadi di wilayah JMA.…”
Section: Permasalahan Komuter Perkotaanunclassified